Controle quimioterápico da mosca Stomoxys calcitrans (Insecta: Muscidae) - Nicolino, Carlos Augusto Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Stomoxys calcitrans (L.) (Diptera: Muscidae) is a serious disorder for ranchers. It is a diptera whose adults (males and females) are hematophagous habits, preferably living in areas close to men and pets, without however invading the homes rural communities. Cause higher annual losses of $ 2 billion to cattle in the United States and $ 100 million in Brazil. Population peaks of S. calcitrans have recently been associated with expanding sugar-alcohol industry in areas of livestock and by-products generated by this large-scale activity. The study was conducted at three farms, each receiving one type of treatment. The first experiment was conducted in the municipality of Miguelópolis / SP, in which we used the treatment of animals with the combination (cypermethrin, chlorpirifos and citronellal) way spraying. The second, held in the city of Guaira, where did the use of diazinon impregnated with earrings. The experiment III was conducted in Barretos / SP, which we used the same drug combination experiment II, this time used to spray the environment of rural property and also used diazinon in the form of earrings, was inserted for fly control . To verify the effectiveness of each experiment counts of flies was performed on days -3, -2 and -1 and +3, +7 and +14. The association used in experiment I reached on the third day after treatment 91.5% effective, that percentage drops significantly until 14 days, which recorded 54.76%. In experiment II were noted efficacies of 72.70% on the third day post-treatment, 73.17% and 67.36% in the second on the last count. Finally, the experiment III efficiencies obtained 83.82%, 71.72% and 83.4% on days +3, +7 and +14 respectively. It was concluded that the best treatment for fly control was the association of treatment facilities in rural and animals (experiment III)

Stomoxys calcitrans (L.) (Diptera: Muscidae) representa um sério transtorno para pecuaristas. É um díptero cujos adultos (machos e fêmeas) possuem hábitos hematófagos, vivendo preferencialmente nas comunidades rurais próximas aos homens e animais domésticos, sem, contudo invadir as residências. Causam perdas anuais superiores a US$ 2 bilhões à bovinocultura nos Estados Unidos e US$ 100 milhões no Brasil. Picos populacionais de S. calcitrans têm sido recentemente associados à expansão da indústria sucroalcooleira em áreas de pecuária e aos subprodutos gerados em larga escala por essa atividade. O estudo foi conduzido em três propriedades rurais, cada um recebendo um tipo de tratamento. O experimento I foi conduzido no Município de Miguelópolis/SP, onde se utilizou o tratamento dos animais com a associação de (cipermetrina, clorpirifós e citronelal) via pulverização. O segundo, realizado no Município de Guaíra, onde se fez o uso de brincos impregnados com diazinon. O experimento III foi conduzido em Barretos/SP, onde se utilizou a mesma associação medicamentosa do experimento II, dessa vez usada para pulverizar o ambiente da propriedade rural e também se usou o diazinon na forma de brincos, inseridos nos animais para o controle da mosca. Para a verificação da eficácia de cada experimento foi realizada contagens das moscas nos dias -3,-2 e -1 e +3,+7 e +14. A associação utilizada no experimento I atingiu no terceiro dia após o tratamento 91,5% de eficácia, percentual que cai significativamente até o 140 dia, onde registrou 54,76%. No experimento II notaram-se eficácias de 72,70% no terceiro dia pós-tratamento, 73,17% na segunda e 67,36% na ultima contagem. Por fim, o experimento III obteve eficácias de 83,82%, 83,4% e 71,72% nos dias +3,+7 e +14 respectivamente. Concluiu-se que o melhor tratamento para o controle da mosca foi à associação do tratamento das instalações rurais e animais (experimento III)
Keywords: Mosca; Mosca - Controle; Diptero; Vinhaça; Quimioterapia; Produtos quimicos; Chemotherapy